A high ionic conductive glass fiber-based ceramic electrolyte system for magnesium‒ion battery application. Issue 9 (15th June 2020) - Singh, Rupali; Janakiraman, S.; Agrawal, Ashutosh; Nayak, Debasis; Ghosh, Sudipto; Biswas, K.
Abstract: The rechargeable magnesium-ion batteries are one of the emerging alternatives of lithium-ion batteries as it has a high volumetric capacity, non-toxic nature and a divalent charge of Mg-ions. The design of an excellent performing magnesium-ion battery requires a stable electrolyte system with high ionic conductivity. However, there is a lack of understanding of how different materials affect the properties of separators in terms of ionic conductivity and stability. In the present study, an attempt has been made to compare the physical and electrochemical characteristics of glass-ceramic and polypropylene membranes as separators in the magnesium-ion battery, using magnesium bis(trifluoromethanesulfonimide) and propylene carbonate as an organic electrolyte. The characterization like X-ray diffraction, field emission electron microscopy, electrolyte uptake, ionic conductivity, voltage stability, thermal stability and transference number are thoroughly examined for both the membranes. The glass-ceramic electrolyte system showed significantly higher ionic conductivity of 9.22 mS cm −1 at room temperature as compared to the polypropylene membrane. Additionally, the glass-ceramic electrolyte system showed higher thermal and voltage stability. Graphical abstract: Image 1